2019
DOI: 10.1002/anie.201911503
|View full text |Cite
|
Sign up to set email alerts
|

A [001]‐Oriented Hittorf's Phosphorus Nanorods/Polymeric Carbon Nitride Heterostructure for Boosting Wide‐Spectrum‐Responsive Photocatalytic Hydrogen Evolution from Pure Water

Abstract: Red phosphorus is a promising photocatalyst with wide visible‐light absorption up to 700 nm, but the fast charge recombination limits its photocatalytic hydrogen evolution reaction (HER) activity. Now, [001]‐oriented Hittorf's phosphorus (HP) nanorods were successfully grown on polymeric carbon nitride (PCN) by a chemical vapor deposition strategy. Compared with the bare PCN and HP, the optimized PCN@HP hybrid exhibited a significantly enhanced photocatalytic activity, with HER rates reaching 33.2 and 17.5 μmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(74 citation statements)
references
References 73 publications
0
70
0
Order By: Relevance
“…2). Whilst most of the work on 2D phases is currently focused on phosphorene, Schusteritsch et al suggested to exfoliate Hittorf's P to give "hittorfene" 73 , and very recently Hittorf-based monolayers 11 and nanostructures 14 were indeed experimentally realised. It is therefore of interest to ask whether this exfoliation can be described by a force field for P, especially as the process involves more complex structures, making the routine application of DFT + MBD more computationally costly than for phosphorene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Whilst most of the work on 2D phases is currently focused on phosphorene, Schusteritsch et al suggested to exfoliate Hittorf's P to give "hittorfene" 73 , and very recently Hittorf-based monolayers 11 and nanostructures 14 were indeed experimentally realised. It is therefore of interest to ask whether this exfoliation can be described by a force field for P, especially as the process involves more complex structures, making the routine application of DFT + MBD more computationally costly than for phosphorene.…”
Section: Resultsmentioning
confidence: 99%
“…White P, known since alchemical times, is formed of weakly bound P 4 molecules 2 , red P is an amorphous covalent network [3][4][5] and black P can be exfoliated to form monolayers, referred to as phosphorene 6,7 , which have promise for technological applications 8 . Other allotropes include Hittorf's violet and Ruck's fibrous forms, consisting of cage-like motifs that are covalently linked in different ways [9][10][11] , P nanorods and nanowires [12][13][14] and a range of thus far hypothetical allotropes [15][16][17][18] . Finally, liquid P has been of fundamental interest due to the observation of a first-order transition between low-and high-density phases [19][20][21] .…”
mentioning
confidence: 99%
“…The application relevance of black phosphorus is most clear in light of its monolayer, phosphorene , but other allotropes are being actively studied as well. For example, monolayer violet phosphorus, dubbed hittorfene , was suggested as a direct‐band gap two‐dimensional (2D) material, and subsequently such samples were indeed experimentally realized, as were nanowires of the same allotrope . Fibrous phosphorus is built from similar tubular fragments as Hittorf's form but exhibits a different extended structure; yet other tubular allotropes can be formed by de‐intercalation from phosphorus‐rich CuI adducts .…”
Section: Figurementioning
confidence: 99%
“…The peak at binding energies of 284.80 eV is related to adventitious C [27] . The peaks of binding energies at 286.25 eV and 288.18 eV are attributed to sp 3 carbon(C−N) in the edges of tri‐s‐triazine unit and sp 2 ‐hybridized carbon (N−C=N), respectively [28] . The C 1s spectra of 3 % ReS 2 /g‐C 3 N 4 presents three peaks originating from C−N (286.10 eV), N−C=N (288.27 eV) and adventitious C (284.80 eV) with similar binding energy positions as g‐C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%